Research progress on the use of polyphenols in the treatment of Crohn’s disease - Zhong, Xianmei; Dai, Qian; Li, Jing; Yang, Jie; Zheng, Xi (Frontiers in Pharmacology, 2025)
Crohn’s disease (CD) is a chronic inflammatory bowel disease (IBD), and its specific etiology is still unclear. However, it is currently widely believed that this disease is the result of interactions among four main factors: host genetic factors, environmental factors, dysbiosis of the gut microbiota, and an abnormal immune system response. In recent years, polyphenolic compounds have become a research hotspot due to their anti-inflammatory, antioxidant, and microbial regulatory properties, demonstrating potential application value in the treatment of CD. This review aimed to explore the mechanism of action of polyphenolic compounds in the treatment of CD, as well as their progress in animal model research and clinical practice.